If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + 3x = (5 + -1x) Remove parenthesis around (5 + -1x) 17 + 3x = 5 + -1x Solving 17 + 3x = 5 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 17 + 3x + x = 5 + -1x + x Combine like terms: 3x + x = 4x 17 + 4x = 5 + -1x + x Combine like terms: -1x + x = 0 17 + 4x = 5 + 0 17 + 4x = 5 Add '-17' to each side of the equation. 17 + -17 + 4x = 5 + -17 Combine like terms: 17 + -17 = 0 0 + 4x = 5 + -17 4x = 5 + -17 Combine like terms: 5 + -17 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| 4k^2+60k+216=0 | | 4n^2+16=-20n | | q=-7x^2+6x+4 | | (n-4)(n-5)=0 | | 10d-22+6y=12d+10 | | mn-x=m | | 0=4x^2-5x-5 | | 0=4x^2+5x-5 | | p=-5x^2+6x+6 | | x+36=x*4 | | 8x+2y+26=10 | | 13x^2+8x-22=0 | | 6+25x=20x+10 | | 5x+2(x+5)=52 | | f(x)=0.7 | | 4+7x=16+x | | (5x)(6y)= | | 6x-3=16x-38 | | 2ln(x+5)=4 | | 100+0.5*(Y-200)+250+200+150= | | 8X+13=-15 | | 2=x-3x+35 | | y=92+-13x | | 5(5p-3)= | | y-1=-13(x-7) | | x^2=13x+30 | | (2x+2y+1)dy+(x+y+1)dx=0 | | M+(m+2)=15 | | 6xy+2y+2=20 | | y=2*t+0.3*sin(2*pi*t) | | 5000m= | | x+2(x-6)+2x+1=124 |